p19-targeted ABD-derived protein variants inhibit IL-23 binding and exert suppressive control over IL-23-stimulated expansion of primary human IL-17+ T-cells - Křížová, Lucie; Kuchař, Milan; Petroková, Hana; Osička, Radim; Hlavničková, Marie; Pelák, Ondřej; Černý, Jiří; Kalina, Tomáš; Malý, Petr (Autoimmunity, 2017)
Interleukin-23 (IL-23), a heterodimeric cytokine of covalently bound p19 and p40 proteins, has recently been closely associated with development of several chronic autoimmune diseases such as psoriasis, psoriatic arthritis or inflammatory bowel disease. Released by activated dendritic cells, IL-23 interacts with IL-23 receptor (IL-23R) on Th17 cells, thus promoting intracellular signaling, a pivotal step in Th17-driven pro-inflammatory axis. Here, we aimed to block the binding of IL-23 cytokine to its cell-surface receptor by novel inhibitory protein binders targeted to the p19 subunit of human IL-23. To this goal, we used a combinatorial library derived from a scaffold of albumin-binding domain (ABD) of streptococcal protein G, and ribosome display selection, to yield a collection of ABD-derived p19-targeted variants, called ILP binders. From 214 clones analyzed by ELISA, Western blot and DNA sequencing, 53 provided 35 different sequence variants that were further characterized. Using in silico docking in combination with cell-surface competition binding assay, we identified a group of inhibitory candidates that substantially diminished binding of recombinant p19 to the IL-23R on human monocytic THP-1 cells. Of these best p19-blockers, ILP030, ILP317 and ILP323 inhibited IL-23-driven expansion of IL-17-producing primary human CD4+ T-cells. Thus, these novel binders represent unique IL-23-targeted probes useful for IL-23/IL-23R epitope mapping studies and could be used for designing novel p19/IL-23-targeted anti-inflammatory biologics.
Keywords: Interleukin-23; interleukin-23 - podjednotka p19; buněčné linie; IL-23; receptory interleukinů; makrofágy; Phagocytes; Dendritic Cells; dendritické buňky; vazba proteinů; Lymphocyte Activation; aktivace lymfocytů; lidé; rekombinantní proteiny; Recombinant Proteins; Macrophages; signální transdukce; fagocyty; Signal Transduction; Interleukin-23 Subunit p19; Cell Line; Models, Molecular; interleukin-23; protein binder; Protein Conformation; T-lymfocyty - podskupiny; molekulární modely; Receptors, Interleukin; konformace proteinů; Th17 cell; T-Lymphocyte Subsets; autoimmune disease; Th17 Cells; Psoriasis; Protein Binding; buňky Th17; Humans